Echocardiographic predictors of presence of cardiac amyloidosis in aortic stenosis . (4th August 2022) - Jaiswal, Vikash; Ang, Song Peng; Chia, Jia Ee; Abdelazem, Eman Muhammad; Jaiswal, Akash; Biswas, Monodeep; Gimelli, Alessia; Parwani, Purvi; Siller-Matula, Jolanta M; Mamas, Mamas A
Abstract: Aims: Aortic stenosis (AS) and cardiac amyloidosis (CA) frequently coexist but the diagnosis of CA in AS patients remains a diagnostic challenge. We aim to evaluate the echocardiographic parameters that may aid in the detection of the presence of CA in AS patients. Method and results: We performed a systematic literature search of electronic databases for peer-reviewed articles from inception until 10 January 2022. Of the 1449 patients included, 160 patients had both AS–CA whereas the remaining 1289 patients had AS-only. The result of our meta-analyses showed that interventricular septal thickness [standardized mean difference (SMD): 0.74, 95% CI: 0.36–1.12, P  = 0.0001), relative wall thickness (SMD: 0.74, 95% CI: 0.17–1.30, P  < 0.0001), posterior wall thickness (SMD: 0.74, 95% CI 0.51 to 0.97, P  = 0.0011), LV mass index (SMD: 1.62, 95% CI: 0.63–2.62, P  = 0.0014), E/A ratio (SMD: 4.18, 95% CI: 1.91–6.46, P  = 0.0003), and LA dimension (SMD: 0.73, 95% CI: 0.43–1.02, P  < 0.0001)] were found to be significantly higher in patients with AS–CA as compared with AS-only patients. In contrast, myocardial contraction fraction (SMD: −2.88, 95% CI: −5.70 to −0.06, P  = 0.045), average mitral annular S′ (SMD: −1.14, 95% CI: −1.86 to −0.43, P  = 0.0017), tricuspid annular plane systolic excursion (SMD: −0.36, 95% CI: −0.62 to −0.09, P  = 0.0081), and tricuspid annular S′ (SMD: −0.77, 95% CI: −1.13 to −0.42, P  < 0.0001) were found to be significantly lower in AS–CA patients. Conclusion: Parameters based on echocardiography showed great promise in detecting CA in patients with AS. Further studies should explore the optimal cut-offs for these echocardiographic variables for better diagnostic accuracy. Graphical Abstract: Graphical Abstract